Effectiveness of Free Association and Thematic Apperception Test in Identifying Antecedent Event: A Case Study - Javaid, Laraib; Asif, Maheen; Zulfiqar, Mishal; Mushtaq, Rehana (Journal of Postgraduate Medical Institute, 2025)
The aim of exploration of the study is to highlight the effectiveness of free association8, and thematic apperception test (TAT)7 in uncovering the antecedent event. This case study was about a 27-year-old male with presenting complaints of repetitive disturbed thought patterns, body shivering, and restlessness. Contrary to his complaints, an antecedent event associated with thoughts was repressed and disturbed his daily life functionality. Findings of assessment uncovered the event as he was being involved in a romantic relationship that led to an intense argument between the client and his brother. Based on bio-psycho-social model case was formulated in which history revealed cognitive inability to process grief and loss, unhealth coping behaviors and excessive rumination as maintaining factors of his problems. A brief intervention plan was devised to enhance daily life functioning of the client by reducing the intensity of thoughts and improve his unhealthy behavior. In the age of advancement where cognitive and behavioral therapies have gained importance, this case report holds its implication to shift the attention of clinical professionals regarding the effectiveness of these assessment modalities.